2018
DOI: 10.1007/s42399-018-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Insulinomas with Minimally Invasive Physical Procedure. Literature Review

Abstract: Insulinoma is the most common functioning pancreatic neuroendocrine tumor with the development of the organic hyperinsulinism and the severe hypoglycemia. Insulinoma can be treated radically only by surgical removal. In cases when the surgery may cause severe complications with the high risk of mortality, the physical non-surgical methods can be used. The world literature review using PubMed, MedScape, and Cochrane databases was performed. Keywords Binsulinoma^+ Bphysical methods^were used including every type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Each method was used because of its availability in the hospital or department. 15 No full head-to-head comparison of different methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each method was used because of its availability in the hospital or department. 15 No full head-to-head comparison of different methods.…”
Section: Discussionmentioning
confidence: 99%
“…22 Kong was the first to use Cyberknife for pancreatic cancer treatment with increased body mass were observed in 100% of cases. 15,23 Phase I/II studies have demonstrated that CyberKnife radiosurgery is a safe and effective strategy for management of patients with locally advanced and metastatic pancreatic cancer. No significant toxicities were observed during or after treatment providing proof of concept that SBRT is an effective therapeutic strategy for functional neuroendocrine neoplasms.…”
Section: Stereotactic Body Radiation Therapy (Sbrt)mentioning
confidence: 99%